Contrast sensitivity and higher-order aberrations in Keratoconus subjects - Einat Shneor (Nature Portfolio, 2021)
Abstract This study analyzes the relationship between contrast-sensitivity and higher-order aberrations (HOA) in mild and subclinical-keratoconus in subjects with good visual-acuity (VA). Keratoconus group (including subclinical-keratoconus) and controls underwent autokeratometry, corneal-tomography, autorefraction and HOA measurement. Contrast-sensitivity was tested using a psychophysical two-alternative forced-choice Gabor patches in three blocks (6, 9, 12 cycles/deg). Controls were compared to the keratoconus group and to a keratoconus subgroup with VA of 0.00 LogMar group ("keratoconus-0.00VA"). Spearman correlation tested association between HOA and contrast-sensitivity. Twenty-two keratoconus subjects (38 eyes: 28 keratoconus, 10 subclinical-keratoconus, 20 keratoconus-0.00VA) and 35 controls were included. There was a significant difference between control and keratoconus, and between control and keratoconus-0.00VA, for keratometry, cylinder, thinnest and central corneal thickness (p < 0.001). Controls showed lower HOA and higher contrast-sensitivity for all spatial-frequencies (p < 0.001). Most HOA were negatively correlated with contrast-sensitivity for all spatial-frequencies for keratoconus group and for 9 and 12 cycles/deg for keratoconus-0.00VA. Keratoconus subjects with good VA showed reduction in contrast-sensitivity and increased HOAs compared to controls. HOA and contrast-sensitivity are inversely correlated in subjects with mild keratoconus despite good VA. This suggests that the main mechanism underlying the decreased vision quality in keratoconus is the increase of HOA.